Juan de Betanzos, the Man Who Boasted Being A Translator - Fossa, Lydia (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThis article draws the linguistic profile of a sixteenth century Colonial translator in the Andes, Juan Díez de Betanzos. This profile covers his linguistic background, and the knowledge of the languages he was in contact with when overseas. The identification and analysis of his translation techniques and strategies form the core of the article. What appears then is the image of the cultural translator of the times, a translator who was also a colonizer, and thus, a linguistic agent of colonization.